Social Security Challenges in Tanzania transforming the present protecting the future - Rwegoshora, Hossea (Dar es Salaam Mkuki na Nyonta, 2014)
Conducting social research requires an understanding of the general theories and principles of social science research. Such knowledge is essential for both social science students and all those undertaking research, evaluating, and designing different intervention strategies to existing social problems. The book is organized around seven main themes, namely: science; logic and objectivity in the social sciences; conceptualization, design and problem definition; types of social science research; sampling and research instruments; data processing and analysis; and theory building and presentation of research findings. Each chapter is treated at length, including illustrative examples from the literature and providing data from the author's own research experience, specifically drawing examples from a variety of Tanzanian social settings.
Includes bibliographies
Keywords: Social Security